IMPLEMENTASI KONSELING INDIVIDU BERBASIS KOGNITIF UNTUK MENINGKATKAN PRESTASI BELAJAR PADA SISWA - Sulistianingsih Sulistianingsih; ine Fajar; muslimah muslimah (UIN Kiai Haji Achmad Siddiq Jember, 2022)
This research study is motivated by the low learning achievement of class X IPS 4 students. This is because the Covid-19 pandemic condition in Indonesia has not been handled so that the learning system in schools used is still online (online). Therefore, it is difficult for homeroom teachers to identify learning problems experienced by their students. Therefore individual counseling can help overcome the problems they are experiencing.This study aims to determine how the implementation and stages of cognitive-based individual counseling services to improve student achievement in class X IPS 4 SMAN 1 Beber. This research is a qualitative research with a phenomenological approach model. The results of this study indicate that the implementation of cognitive-based individual counseling to improve student achievement in class X IPS 4 at SMAN 1 Beber has been running well and optimally. Although in its implementation there are obstacles including the limited time and facilities in providing cognitive-based individual counseling services to improve student achievement in class X IPS 4 SMA Negeri 1 Beber. This is because of the good cooperation between the BK teacher and the principal and homeroom teacher or other staff at SMA Negeri 1 Beber. Furthermore, the stages of implementing cognitive-based individual counseling to improve student achievement in class X IPS 4 SMAN 1 Beber are in accordance with the stages that have been planned together. These stages include the planning stage, the implementation stage, the activity evaluation stage, the follow-up stage, and the reporting stage.